COMPARISON OF KINETIC TEST RESULTS USING FREE DRAINING COLUMN LEACH TEST METHOD ON LABORATORY SCALE AND FIELD SCALE FOR MIXING OF PAF AND FLY ASH MATERIAL SCENARIO (CASE STUDY: PT ARUTMIN INDONESIA) - Karlina Inggarini, Dhea
The method of mixing materials that have the potential to form acid (Potentially Acid Forming/PAF) and materials that do not have the potential to form acid (Non- Potentially Acid Forming/NAF) can be applied as a method of preventing the formation of acid mine drainage. In this study, the coal ash of the PLTU Asam-Asam was used as a material that does not have the potential to form acid and PAF material from the mining site of PT Arutmin Indonesia. The research scenario is carried out by varying the amount of fly ash, then physical tests, elemental and mineralogy tests, static tests and kinetic tests will be carried out for field and laboratory scales. An analysis was carried out for each mixing scenario using a material balance for laboratory or field scale, carried out by comparing the proportions of PAF and NAF weight using the Net Acid Producing Potential (NAPP) value in kg H2SO4/ton of rock, this will then be analyzed further by the results of the kinetic tests that have been carried out. The kinetic test was carried out using the free draining column leach test method, in the laboratory scale kinetic test in the 5% mixing scenario, a low increase in the pH value was obtained when compared to the pH value of the control column. 101.44% on 1-day cycle, 133.18% on 3-day cycle and 75.94% on 7-day cycle. For the field scale kinetic test, the tendency of changes in pH and NAPP values has the same trend as the laboratory scale, the pH value will increase as the NAPP value decreases. For laboratory and field scale kinetic tests with 5%, 15% and 25% mixing scenarios, the results of laboratory scale kinetic tests result in an increase in pH value which tends to be more gentle when compared to the increase in pH value on a field scale. the wet cycle and dry cycle are more controlled, besides the homogeneity of a more uniform mixture also affects the value of the pH test results. For the field scale, the wet and dry cycles occur according to local weather conditions without any specific engineering, this is certainly more uncontrolled than the laboratory scale.